1994
DOI: 10.1177/089686089401400409
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Steroids and Malnutrition in Chronic Renal Failure

Abstract: Objective To determine whether anabolic steroids are useful in the management of the malnutrition of chronic renal failure. Data Source Original research studies and book chapters about anabolic steroids and their use in uremia and various illnesses associated with malnutrition. We included studies that describe the benefits of anabotic steroids in the treatment of anemia and sexual dysfunction of chronic renal failure. Forty-two such studies were published between 1942 and 1992. Results Anabolic steroids impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There is interest in the potential value of anabolic steroids for the treatment of this problem. Soliman and Oreopoulos (19) published a review of the literature dealing with anabolic steroids given to patients with acute or chronic renal failure and concluded that some patients had experienced nutritional benefit from androgen administration. They argued that anabolic steroids should be evaluated more carefully for the treatment of malnutrition.…”
Section: Anabolic Steroids and Nutrition In Chronicmentioning
confidence: 99%
“…There is interest in the potential value of anabolic steroids for the treatment of this problem. Soliman and Oreopoulos (19) published a review of the literature dealing with anabolic steroids given to patients with acute or chronic renal failure and concluded that some patients had experienced nutritional benefit from androgen administration. They argued that anabolic steroids should be evaluated more carefully for the treatment of malnutrition.…”
Section: Anabolic Steroids and Nutrition In Chronicmentioning
confidence: 99%
“…Androgenic steroids, such as nandrolone decanoate, have improved nutritional parameters through their anabolic effects, hence increasing lean body mass and improving nitrogen balance. [39][40][41] Recombinant human growth hormone has well-established anabolic properties. It promotes protein synthesis, decreases protein degradation, enhances lipolysis, and increases food conversion.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…45 Based on several preliminary studies, the use of anabolic steroids and growth factors for treatment of malnutrition may be promising. [39][40][41][46][47][48][49][50] However, whether use of these agents will result in long-term improvement in nutritional indexes, morbidity, and mortality must be clarified by further studies.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Several studies have recently shown that admin istration of recombinant human growth hormone (rHGH) or insulinlike growth factor-1 (IGF-1) can improve nutritional parameters (for example, increased serum albumin, transferrin) (8,16,70,71). However, use of these hormones is still in the experimental stage.…”
Section: Prevention and Treatment Of Malnutritionmentioning
confidence: 99%